Electrochemical investigation of gold uptake from chloride solution by magnetite - Alorro, Richard; Hiroyoshi, N.; Kijitani, H.; Ito, M.; Tsunekawa, M. (Taylor and Francis Inc., 2015)
An electrochemical method (potential sweep method) was utilized to investigate the nature of the absorbed gold on magnetite and to determine the gold sorption mechanism. A magnetite electrode was prepared in the laboratory, made in contact with a gold chloride solution at different conditions, and was subjected to cyclic voltammetry. The cyclic voltammogram of the magnetite electrode pretreated in a gold chloride solution recorded an anodic current peak at around 1.0 V (vs. Ag/AgCl), which corresponds to the current generated for the anodic dissolution of metallic gold in a chloride medium. The results of the electrochemical experiments suggest that gold chloride complexes are reduced to metallic gold on the surface of magnetite. A four-stage gold uptake mechanism was proposed: (i) the transport of AuC14- from the bulk solution to the magnetite surface, (ii) adsorption of AuC14- ions on magnetite surface by electrostatic attraction, (iii) electrochemical reduction of AuC14- to metallic Au, and (iv) the transport of soluble species to the solution phase. The electrochemical investigation also revealed that Fe3+ ions released from magnetite into the solution, suppressed the gold uptake at the acidic pH region.